Emotional Reactions of Professionals to Challenging Behaviors in People with Intellectual and Developmental Disability - Juliana Reyes-Martín; David Simó-Pinatella; Ana Andrés (Behavioral Sciences, 2024)
Professionals working with people with intellectual and developmental disability (IDD) can be exposed to challenging behaviors (CBs), which may result in professionals exhibiting emotional reactions that can impact their practices. This study examined these reactions and analyzed how they are influenced by the individual characteristics of people with IDD (gender, age, and level of IDD) and the variables related to CB (type of behavior and its frequency and behavioral function). A total of 125 professionals assessed 293 people with IDD who exhibited CBs. The professionals were asked to complete the Behavior Problems Inventory—Short Form, the Emotional Reactions to Challenging Behavior Scale, and the Questions About Behavior Function measure. It was revealed that positive emotional reactions predominated over negative ones. Significant results were found regarding the level of disability and the age of people with IDD. Emotional reactions were related to the severity of CBs, especially self-injurious and aggressive/destructive behavior, as well as certain behavioral functions. The severity of CBs and the age of people with IDD emerge as key predictors of the emotional reactions of professionals. In short, these reactions vary according to different variables, highlighting the importance of interventions that address professionals’ emotional needs.